Multiphoton Imaging of Collagen, Elastin, and Calcification in Intact Soft‐Tissue Samples. Issue 1 (31st October 2018) - Gade, Piyusha S.; Robertson, Anne M.; Chuang, Chih‐Yuan
Abstract: Multiphoton‐induced second‐harmonic generation and two‐photon excitation enable imaging of collagen and elastin fibers at micron‐level resolution to depths of hundreds of microns, without the use of exogenous stains. These attributes can be leveraged for quantitative analysis of the 3D architecture of collagen and elastin fibers within intact, soft tissue specimens such as the artery and bladder wall. This architecture influences the function of intramural cells and also plays a primary role in determining tissue passive mechanical properties. Calcification deposition in soft tissues is a highly prevalent pathology in both older and diseased populations that can alter tissue properties. In this unit, we provide a protocol for simultaneous multiphoton microscopy (MPM) imaging and analysis of 3D collagen and elastin structures with calcification, which is effective for fixed and fresh intact samples. We also provide an associated micro‐CT protocol to identify regions of interest in the samples as a means to target the MPM imaging. © 2018 by John Wiley & Sons, Inc.